Analisis Stilistika dan Nilai Moral dalam Novel Nyanyian Gurukinayan Karya Albert Purba Serta Relevansinya terhadap Pembelajaran : Stylistic Analysis and Moral Values in the Novel Nyanyian Gurukinayan by Albert Purba and Its Relevance to Learning - Lumban Gaol, Tetty Mayarni; Simaremare , Juni Agus; Br Saragih, Renita (Information Technology and Science(ITScience), 2025)
The use of language, especially stylistics in a literary work, is an important aspect of forming meaning. This study aims to describe stylistics, especially in the components of rhetorical devices and moral values, in the novel Nyanyian Gurukinyan by Albert Purba. This study uses a qualitative approach with a descriptive method. The results of this study answer three problem formulations, namely: (1) the use of stylistics, especially in the components of rhetorical devices in the novel Nyanyian Gurukinyan by Albert Purba, (2) the moral values ?? contained in the novel, and (3) its relevance to Indonesian language learning at SMAS Katolik Mariana. The study found 47 uses of figures of speech, consisting of 11 similes, seven metaphors, and 29 personifications. In addition, 11 structural investigations were found, consisting of 2 repetitions, three parallelisms, and six hyperboles. The analysis also identified 34 images, including 11 auditory, four olfactory, nine visual, and 10 movement images. Regarding moral values, 11 data points showed the relationship between humans and God, 11 data points on relationships between fellow humans, 2 data points on the relationship between humans and nature, and 2 data points related to the relationship between humans and themselves. The results of this study were then made relevant to learning Indonesian at SMAS Katolik Mariana through simple teaching materials. Based on the questionnaires distributed, it can be concluded that the results of this study can be applied to learning Indonesian at the school.